The Contribution of Cognitive Distortions in Predicting Achievement Motivation among Grade 11th Students in Al Sharqiyah North Governorate, Sultanate of Oman - Lawati, Esam; Benkouider, Amina; Masrouri, Jokha (International Journal of Psychology, 2024)
Purpose: The Contribution of Cognitive Distortions in predicting achievement motivation among Grade 11th Students in Al Sharqiyah North Governorate in the Sultanate of Oman is to determine the extent to which cognitive distortions predict achievement motivation among eleventh-grade students in North Al Sharqiyah Governorate in the Sultanate of Oman. Methodology: This is accomplished by determining students' levels of cognitive distortions and achievement motivation, and then investigating the straightforward linear link between cognitive distortions and accomplishment motivation. In addition to demonstrating statistically significant variations in cognitive distortions and levels of achievement motivation based on gender and academic specialty. The study sample consisted of (404) grade 11 students enrolled in public schools in the Sultanate of Oman's North Al Sharqiyah schools during the academic year 2021/2022 AD. The Achievement Motivation Scale for Children and Adults by Harmans (1987), and the Cognitive Distortions Scale created by Saladin (2015). Results: The researchers have found the significance level of the regression model is less than 0.05, and they are statistically significant, hence the model has statistical significance and can predict the relationship between cognitive distortions and achievement motivation. The result also indicates that no differences in the level of cognitive distortions as a whole depending on the gender variable, in addition, the result shows that the cognitive structures that the individual builds about himself/herself and the world are not affected by the type of specialization that student’s study. The result indicates that the achievement motivation of the sample members is not affected by gender as well as the difference in the academic specialization of the student’s study. Unique Contribution to Theory, Practice and Policy: The study recommended several significant recommendations: focusing on psychological counselling for students, regardless of their gender and cognitive levels, as well as introducing group counselling programs that work to improve the motivation to achieve and target cognitive distortions, and finally, conducting more research on the study variables.